Environmental factors determining the distribution of highland plants at low‐altitude algific talus sites. Issue 2 (3rd January 2017) - Wakui, Akimi; Sueyoshi, Masanao; Shimokawabe, Ayuma; Kudo, Gaku; Morimoto, Junko; Nakamura, Futoshi
Abstract: Algific talus is a micro‐scale habitat type where highland plants (subalpine and alpine species) are found, disjunct from their typical range, in lowland forests. On algific talus, cold airflows from the interstices between talus fragments create a local microclimate colder than surrounding forests. Despite of the widely‐known occurrence of unique vegetation on algific talus, critical environmental factors determining the distribution of highland species in this habitat type are unclear. In order to reveal the environmental factors enabling highland species to inhabit algific talus, we investigated the vegetation and environments of 26 algific talus sites and four reference (non‐algific talus) sites in Hokkaido, northern Japan. Several algific talus sites were dominated by highland species, while some algific talus sites and all non‐algific talus sites were dominated by lowland species. Community analysis based on detrended correspondence analysis (DCA) and canonical corresponding analysis (CCA) revealed that the algific talus sites dominated by highland species had lower ground temperature, more acidic soil, larger canopy openness, and less diverse vegetation than the sites dominated by lowland species. Highland plants might be maintained under conditions stressful for lowland plants, resulting in less competitive situation. Generalized linear models (GLM), used to evaluate the response of individual highland species to environmental factors, revealed that preferable environmental conditions for highland plants are highly species specific. These results indicate that the maintenance of diverse environments is crucial for the conservation of the unique vegetation and local populations of highland species in algific talus areas.